The Effect Of Cognitive Competency On Early Adolescent Digital Literation Skills - Pratiwi Kartika Sari; Nurudin Siraj; Nadia Fatmalia (EDUCATIO : Journal of Education, 2025)
This study aims to see the effect of cognitive competency levels C1-Knowledge, C2-Comprehension, and C3-Application on digital literacy skills in early adolescents. In this study cognitive competence is limited to three aspects, such as knowledge, understanding, and application. The research method used a survey by looking at the effect using simple regression analysis. The results showed that the cognitive competency level of knowledge in digital literacy skills was in the top position of 97.0%, the level of application cognitive competence in digital literacy skills was in the second position of 89.0%, the level of cognitive competence in understanding digital literacy skills was in the third position of 80. , 3%. The conclusion in this study is that there is an effect of cognitive competence on digital literacy skills of early adolescents with a knowledge level of C1-Knowledge 97.0% It shows the concept of students' digital literacy skills in remembering and storing information very well, understanding C2-Understanding 80.3% Shows the concept of students 'digital literacy skills in understanding and choosing information well, C3-Application 89.0% Shows the concept of students' digital literacy skills in applying (using) information well.